E-Marketing Model For A Globally Competitive Micro, Small And Medium-Sized Enterprise Sector: Insights From Nigeria - Okpara, Gazie S.; Agu, Godswill; Onyeokoro, Sunday C. (Marketing and Business Strategy, 2025)
Nigeria, particularly its southeastern region, is home to numerous micro, small, and medium enterprises (MSMEs) that contribute significantly to the nation's economy. Despite facing various challenges, MSMEs account for 84% of total employment and contribute 48.47% to Nigeria’s GDP, according to the Small and Medium Enterprises Development Agency of Nigeria and the National Bureau of Statistics (2013). However, these enterprises struggle with limited patronage and low global competitiveness, largely due to restricted access to modern technology. This study emphasizes the urgent need for a strategic, modern marketing approach to boost the visibility and acceptance of made-in-Nigeria products. It proposes a 5Ps marketing model product, price, place, promotion, and people integrated within a modified Technology Acceptance Model (TAM). The study explores MSMEs’ awareness, drivers, and intentions to adopt e-marketing strategies. Using SmartPLS structural equation modeling on data from 181 respondents, the research confirms that the 5Ps, along with perceived usefulness, perceived ease of use, and attitude, significantly influence the intention to adopt e-marketing. The study offers both theoretical insights and practical recommendations to enhance MSMEs’ marketing capabilities, increase customer engagement, and improve the adoption of digital strategies necessary for global competitiveness.